Calla Lily (Zantedeschia aethiopica (L.) Spreng) as a Bioremediation Agent of Jatibarang Landfill Leachate Conterminated Waters - Maria Ulfah; Luhur Pujo Santoso; Atip Nurwahyunani (School of Postgraduate Studies, Diponegoro Univer, 2025)
The leachates are formed when the waste mixes with the water and penetrates into the ground. Leachate has a dangerous impact because it contains toxic organic/inorganic pollutants, heavy metals and ammonia. Many problems will arise if the leachate is not treated and left alone. The pollutants from landfill leachate have accumulative and detrimental effect on the ecology and food chains. Bioremediation effectively heals the environment when it's been contaminated by pollutants and toxics. The purpose of this study was to determine the effectiveness of Calla Lily (Zantedeschia aethiopica (L.) Spreng) as a BOD and leachate turbidity removal. This type of research is qualitative research and is presented descriptively. Based on the results of the research, it was shown that calla lily were able to reduce BOD and turbidity removal, but the treatment had no significant effect. The results of the analysis showed that the physical and chemical parameters of leachate at Jatibarang landfill that exceeded the leachate quality standards were BOD 464 mg/L (9.2% removal), turbidity removal 6.3 NTU (96.23% removal). If the leachate is only collected without further treatment, it will result in the leachate entering residential rivers and contaminating the well water in the surrounding Jatibarang area and possibly causing health problems.